Cultural Translation as Representation in Paul Bowles’ Their Heads Are Green and Their Hands Are Blue (1957) - Aammari Lahoucine (Romanian Journal of English Studies, 2017)
This paper is premised upon the American writer, Paul Bowles, and his journey into Morocco as a liminal topography. In his Their Heads are Green and their Hands are Blue the traveller-writer crosses borders, moving from the metropolis to the colony as a far-flung territory, a process which is faced with a sense of unrepresentability of the Other and its culture, leading to a sense of dislocation on the part of the traveller. The latter lives on the edge of two starkly different cultures, civilizations, religions and societies. His peregrination produces weird feelings which are associated with the liminal and the threshold, and which oscillate between the homely and unhomely, the ordinary and the mysterious.